1998
DOI: 10.1161/01.hyp.31.5.1146
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With Enalapril Modifies the Pain Perception Pattern in Hypertensive Patients

Abstract: Abstract-The cardiovascular system shares numerous anatomic and functional pathways with the antinociceptive network. The aim of this study was to investigate whether angiotensin-converting enzyme (ACE) inhibitor treatment could affect hypertension-related hypalgesia. Twenty-five untreated hypertensive patients, together with a control group of 14 normotensive subjects, underwent dental pain perception evaluation by means of a pulpar test (graded increase of test current applied to healthy teeth). After the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…Hypertension-related hypoalgesia has been variously described as a cause, consequence, and correlate of blood pressure, 16 with some justification for each perspective. For example, Guasti et al 30 found that pharmacological treatment of hypertension increased sensitivity to dental pain, implying that hypoalgesia is a product of increased blood pressure. On the other hand, Ghione et al 31 found no effect of successful antihypertensive treatment on pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension-related hypoalgesia has been variously described as a cause, consequence, and correlate of blood pressure, 16 with some justification for each perspective. For example, Guasti et al 30 found that pharmacological treatment of hypertension increased sensitivity to dental pain, implying that hypoalgesia is a product of increased blood pressure. On the other hand, Ghione et al 31 found no effect of successful antihypertensive treatment on pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Guasti et al, 164 using dental pain perception evaluation by means of a pulpar test, showed that the pain threshold was significantly higher in hypertensive than in normotensive subjects. However, the pain threshold and tolerance in the patients decreased to levels similar to those of normotensives during treatment with enalapril.…”
Section: Looking Beyond Ace Inhibitionmentioning
confidence: 99%
“…Over two decades of research have established the phenomenon of hypertensive hypoalgesia (for review see Ghione, 1996). Numerous studies have documented that, compared to individuals with blood pressure in the normal range, patients with hypertension are characterised by reduced pain in response to various forms of noxious stimulation, including electrical tooth pulp (e.g., Guasti, Grimoldi, Diolisi, Rosaria, Petrozzino, Gaudio, Grandi, Rossi, & Venco, 1998), thermal (e.g., Sheps, Bragdon, Flint Gray, Ballenger, Usedom, & Maixner, 1992), and electrocutaneous (e.g., Rosa, Vignocchi, Panattoni, Rossi, & Ghione, 1994) stimulation.…”
Section: Introductionmentioning
confidence: 99%